2012
DOI: 10.1038/onc.2012.99
|View full text |Cite
|
Sign up to set email alerts
|

The Rac1 splice form Rac1b promotes K-ras-induced lung tumorigenesis

Abstract: Rac1b, an alternative splice form of Rac1, has been previously shown to be upregulated in colon and breast cancer cells, suggesting an oncogenic role for Rac1b in these cancers. Our analysis of NSCLC tumor and matched normal tissue samples indicates Rac1b is upregulated in a significant fraction of lung tumors in correlation with mutational status of K-ras. To directly assess the oncogenic potential of Rac1b in vivo, we employed a mouse model of lung adenocarcinoma, in which the expression of Rac1b can be cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
88
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 20 publications
4
88
0
Order By: Relevance
“…Moreover, RAC1b overexpression has been implicated in the induction of EMT (40,41). EMT is a form of epithelial plasticity that has been associated with tumor metastasis and, accordingly, RAC1b was reported to have a key role in the malignant progression of breast and lung tumors (28,36,41). Our finding that RAC1b overexpression significantly associates with a poor outcome in PTCs may be indicative of a similar role for RAC1b in the progression of thyroid carcinomas.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Moreover, RAC1b overexpression has been implicated in the induction of EMT (40,41). EMT is a form of epithelial plasticity that has been associated with tumor metastasis and, accordingly, RAC1b was reported to have a key role in the malignant progression of breast and lung tumors (28,36,41). Our finding that RAC1b overexpression significantly associates with a poor outcome in PTCs may be indicative of a similar role for RAC1b in the progression of thyroid carcinomas.…”
Section: Discussionsupporting
confidence: 57%
“…It was first identified in skin and epithelial tissue of the intestinal tract (26). RAC1b expression was also documented in breast tissue and was found to be overexpressed in colorectal and lung cancer (23,26,27,28).…”
Section: Introductionmentioning
confidence: 99%
“…One particular example is the tumor-related splicing variant Rac1b, an isoform of the signaling GTPase Rac1 (Matos et al 2003), in which a usually skipped exon 3b is retained. The resulting protein isoform Rac1b is overexpressed in a specific subtype of colorectal tumors and required to sustain tumor cell survival (Jordan et al 1999;) but was also reported in breast, lung, and thyroid tumors (Schnelzer et al 2000;Radisky et al 2005;Liu et al 2012;Stallings-Mann et al 2012;Silva et al 2013;Zhou et al 2013). Interestingly, Rac1b was found to be predominantly in the signaling-competent GTP-bound conformation (Schnelzer et al 2000;Matos et al 2003;Fiegen et al 2004;Radisky et al 2005), so that small changes in its expression level yield significant cellular responses.…”
Section: Introductionmentioning
confidence: 99%
“…155 Expression of Rac1b has also been found in breast cancer and lung cancer. 156,157 Rac1b has been shown to be involved in MMP-3-mediated malignant transformation of mammary epithelial cells. MMP-3 induces the expression of Rac1b which increases the levels of cellular ROS, leading to expression of the transcription factor Snail, which induces epithelial-mesenchymal transition (EMT) as well as oxidative damage to DNA and genomic instability.…”
mentioning
confidence: 99%